Mobile learning and its effectiveness in mathematics. Issue 1 (March 2021) - Yosiana, Y; Djuandi, D; Hasanah, A
Abstract: Mobile Learning is a development approach to distance learning. Extensive access to all mobile devices and unlimited learning opportunities for space and time, making mobile learning a critical role in the learning process. The purpose of this study is to determine how the characteristics of effective mobile learning based on the results of previous studies and to get an overview of the effectiveness of mobile learning in mathematics in senior high school. The method used in this study is an evaluative survey method with library research and field surveys. This study involved 75 eleventh grade students in one of the senior high schools in West Bandung District. The instruments used are questionnaires and interviews. Statistical analysis results show that the effectiveness of mobile learning in math learning is at a middle level. Based on the results of the survey can be concluded that the implementation of mobile learning on learning is an effective way of delivering mathematical content and able to impart self-reliance for students in enhancing the ability to understand the subject of his studies.